Use of water-soluble curcumin in TPS/PBAT packaging material: interference on reactive extrusion and oxidative stability of chia oil - Mücke, Naiara (2018)
The reactive extrusion technique is efficient in the incorporation of bioactive compounds for active packaging development. The application of curcumin, a strong antioxidant in its pure, isolated form to obtain active packaging has already been investigated; however, the use of water-soluble curcumin (WSC) in thermoplastic starch/poly(butylene adipate-co-terephthalate) (TPS/PBAT) films has not yet been investigated. It is important to determine how WSC would affect starch esterification reaction during reactive extrusion (REx). The use of WSC at 0.5%wt led to an increase in tensile strength, elongation at break, and Young’s modulus. A reduction in starch esterification was observed; however, an improvement in TPS/PBAT compatibility was detected by infrared spectroscopy, X-ray diffraction, and scanning electron microscopy images. It is worth noting that WSC addition resulted in an increase in the film’s solubility and water vapor permeability, due to the hydrophilic character of the WSC. The films were used to package chia oil, and the oxidative stability data were evaluated by UV-Vis spectroscopy coupled with principal component analysis. The addition of WSC (0.5%wt) in the films led to the improvement of the oil oxidative stability, suggesting that using water-soluble curcumin may be a promising alternative to active packaging in the case of reactive extruded films.